Review of historical earthquakes and survey of active faults in the San Leonardello Graben area, Mt. Etna (Sicily) - CARVENI, Pietro; BENFATTO, Santo; IMPOSA, Sebastiano; MANISCALCO, Rosanna; SALLEO PUNTILLO, Maria; STURIALE, Giovanni (Contributions to Geophysics and Geodesy, 2011)
Mount Etna is the largest active volcano in Europe, grown by accumulation of lavas and pyroclastics erupted by numerous vents during the last 180 kyr. It is located along the Ionian coast of Sicily, on the margin of two main structural domains: the Apennine-Maghrebian Chain to the north and the Hyblaean Foreland to the south. While eastern Sicily is characterized by a general uplift, the sector bounded by the North- East Rift and the Pernicana Fault northward, and by the Montagnola-Aci Castello Fault System toward SW is lowering; three more fault systems are active in the eastern sector of Etna: i) the Giardini-Mascali Fault System (NE–SW and NNE–SSW trends); ii) the Ripa della Naca-Piedimonte Fault System (NE–SW trend); iii) the Timpe Fault System (NNW–SSE trend). In historical times, the Giardini-Mascali Fault System was active only in 1847, while the Ripa della Naca-Piedimonte Fault System was active before and during the 1865, 1928 and 1971 eruptions. Several earthquakes have occurred along the Timpe Fault System from 1805 to present. The analysis of seismological data and volcanic activity shows that the Timpe Fault System is the most active of the eastern flank of Etna. The most important faults of this system are the Moscarello, San Leonardello and Macchia-Stazzo Faults forming the San Leonardello Graben. Shallow earthquakes occur along these faults, frequently causing surface fractures. In this paper we analyze historical records of earthquakes stronger than VII degree EMS-98. Macroseismic data are available since 1805. The epicenters are located along the northernmost segment of the faults. Along these faults offsets are mainly vertical with the maximum value of 80 cm recorded along the Moscarello Fault after the 1911 Fondo Macchia Earthquake.